DI-029 Quality of information on male fertility in the summary of product characteristics – cause for concern. (24th March 2015) - Pompe, SV; Strobach, D; Becker, A; Andraschko, M; Stief, C; Trottmann, M
Abstract : Background: Reasons for male infertility are manifold and often not clearly identifiable; drug treatment can be a contributing factor. Retrospective analysis of 378 men wishing to father a child revealed drug consumption in 43.4%. 1 Detailed information about drugs affecting male fertility is essential for counselling of physicians and patients. According to European guidelines the Summary of Product Characteristics (SmPC) should include specific information on this topic. 2 Purpose: To study the quality of information given in SmPCs on the effect of drugs on male fertility. Material and methods: The SmPC should contain information on the effect on male fertility under headings 4.6 (Fertility, pregnancy and lactation) and 5.3 (Preclinical safety data). 2 The current German SmPCs of 124 drugs were examined for the required information and details were differentiated by gender. SmPCs were obtained from www.fachinfo.de or company web sites. Results: Of the 124 SmPCs 41 mentioned male fertility under heading 4.6. Under heading 5.3 82 mentioned reproductive studies, 29 gave no information, 8 times no studies existed and 5 gave incomplete information. Only 10 mentioned male fertility directly, 14 referred to male and female fertility, 35 used the term "fertility". In 12 cases data on fertility/reproduction were only presented elsewhere in the SmPC (not 4.6/5.3). SmPC contained no information at all on fertility in 47 cases, despite some of them mentioning reproductive studies. Conclusion: Data on the effect of drugs on male fertility presented in the SmPC are incomplete and in many cases not in line with requirements of the European guideline. General statements on "fertility" without male/female distinction are not helpful since the reproductive capability of women and men differs in many aspects. References: Pompe, et al. Arzneimittelkonsum bei Männern mit unerfülltem Kinderwunsch. J Urol Urogynäkol 2014;21:32–3 European Commission. A Guideline on summary of product characteristics (SmPC). September 20 No conflict of interest.